Vascular effects of maternal alcohol consumption - Ramadoss, Jayanth (American Physiological Society, 2012)
Maternal alcohol consumption during pregnancy is a significant field of scientific exploration primarily because of its negative effects on the developing fetus, which is specifically defined as fetal alcohol spectrum disorders. Though the effects on the mother are less explored compared with those on the fetus, alcohol produces multiple effects on the maternal vascular system. Alcohol has major effects on systemic hemodynamic variables, endocrine axes, and paracrine factors regulating vascular resistance, as well as vascular reactivity. Alcohol is also reported to have significant effects on the reproductive vasculature including alterations in blood flow, vessel remodeling, and angiogenesis. Data presented in this review will illustrate the importance of the maternal vasculature in the pathogenesis of fetal alcohol spectrum disorders and that more studies are warranted in this field.